Statement of the German Roentgen Society, German Society of Neuroradiology, and Society of German-speaking Pediatric Radiologists on Requirements for the Performance and Reporting of MR Imaging Examinations Outside of Radiology - Hunold, Peter; Bucher, Andreas Michael; Sandstede, Joern; Janka, Rolf Matthias; Fritz, Lars Benjamin; Regier, Marc; Loose, Reinhard; Barkhausen, Joerg; Mentzel, Hans-Joachim; Zimmer, Claus; Antoch, Gerald; Schoenberg, Stefan O.; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Magnetic Resonance Imaging (MRI) is a very innovative, but at the same time complex and technically demanding diagnostic method in radiology. It plays an increasing role in high-quality and efficient patient management. Quality assurance in MRI is of utmost importance to avoid patient risks due to errors before and during the examination and when reporting the results. Therefore, MRI requires higher physician qualification and expertise than any other diagnostic imaging technique in medicine. This holds true for indication, performance of the examination itself, and in particular for image evaluation and writing of the report. In Germany, the radiologist is the only specialist who is systematically educated in all aspects of MRI during medical specialty training and who must document a specified, high number of examinations during this training. However, also non- radiologist physicians are increasingly endeavoring to conduct and bill MRI examinations on their own.
CRIS-Team WoS Importer:2021-05-21